Cross-Sectional Analysis of the Cisanggarung River Against Flooding in Babakan Village Using the HEC-RAS Program - Fadhli Dzil Ikram; Muhammad Ghafar Franandi; Akyono Akyono; Awliya Tribhuwana (Riviera Publishing, 2025)
Floods are hydrometeorological disasters that significantly affect communities, infrastructure, and the environment. This study aims to assess the capacity of the Cisanggarung River to accommodate flood discharge flow using HEC-RAS software. The analysis was based on rainfall data from three observation stations: Losari Station, Cangkuang Station, and Gebang Station. The research utilized frequency analysis, probability distribution tests, and hydrological and hydraulic simulations to evaluate the river's ability to handle floodwaters. The findings indicated that the current cross-section of the Cisanggarung River is insufficient to accommodate the planned flood discharge of 904.8 m³/sec, suggesting the need for river normalization efforts. This study provides critical insights for flood mitigation strategies, including infrastructure improvements and watershed management optimization. By implementing effective mitigation measures, the risk and impact of flooding in the region can be significantly reduced, contributing to improved flood resilience and urban planning.